A deep-learning workflow to predict upper tract urothelial carcinoma protein-based subtypes from H&E slides supporting the prioritization of patients for molecular testing - Angeloni, Miriam; van Doeveren, Thomas; Lindner, Sophia; Volland, Patrick; Schmelmer, Jorina; Foersch, Sebastian; Matek, Christian; Stöhr, Robert; Geppert, Carol-Immanuel; Heers, Hendrik; Wach, Sven; Taubert, Helge; et al. (Journal of Pathology: Clinical Research, 2024)
Upper tract urothelial carcinoma (UTUC) is a rare and aggressive, yet understudied, urothelial carcinoma (UC). The more frequent UC of the bladder comprises several molecular subtypes, associated with different targeted therapies and overlapping with protein-based subtypes. However, if and how these findings extend to UTUC remains unclear. Artificial intelligence-based approaches could help elucidate UTUC's biology and extend access to targeted treatments to a wider patient audience. Here, UTUC protein-based subtypes were identified, and a deep-learning (DL) workflow was developed to predict them directly from routine histopathological H&E slides. Protein-based subtypes in a retrospective cohort of 163 invasive tumors were assigned by hierarchical clustering of the immunohistochemical expression of three luminal (FOXA1, GATA3, and CK20) and three basal (CD44, CK5, and CK14) markers. Cluster analysis identified distinctive luminal (N = 80) and basal (N = 42) subtypes. The luminal subtype mostly included pushing, papillary tumors, whereas the basal subtype diffusely infiltrating, non-papillary tumors. DL model building relied on a transfer-learning approach by fine-tuning a pre-trained ResNet50. Classification performance was measured via three-fold repeated cross-validation. A mean area under the receiver operating characteristic curve of 0.83 (95% CI: 0.67–0.99), 0.8 (95% CI: 0.62–0.99), and 0.81 (95% CI: 0.65–0.96) was reached in the three repetitions. High-confidence DL-based predicted subtypes showed significant associations (p < 0.001) with morphological features, i.e. tumor type, histological subtypes, and infiltration type. Furthermore, a significant association was found with programmed cell death ligand 1 (PD-L1) combined positive score (p < 0.001) and FGFR3 mutational status (p = 0.002), with high-confidence basal predictions containing a higher proportion of PD-L1 positive samples and high-confidence luminal predictions a higher proportion of FGFR3-mutated samples. Testing of the DL model on an independent cohort highlighted the importance to accommodate histological subtypes. Taken together, our DL workflow can predict protein-based UTUC subtypes, associated with the presence of targetable alterations, directly from H&E slides.
CRIS-Team Scopus Importer:2024-03-29
Keywords: deep-learning; digital pathology; immunohistochemistry; protein-based subtypes; targeted therapy; upper tract urothelial carcinoma; whole slide images

AI allows pre-screening of FGFR3 mutational status using routine histology slides of muscle-invasive bladder cancer. - Bannier, Pierre Antoine; Saillard, Charlie; Mann, Philipp; Touzot, Maxime; Maussion, Charles; Matek, Christian; Klümper, Niklas; Breyer, Johannes; Wirtz, Ralph; Sikic, Danijel; Schmitz-Dräger, Bernd; Wullich, Bernd; et al. (Nature Communications, 2024)
Pathogenic activating mutations in the fibroblast growth factor receptor 3 (FGFR3) drive disease maintenance and progression in urothelial cancer. 10-15% of muscle-invasive and metastatic urothelial cancer (MIBC/mUC) are FGFR3-mutant. Selective targeting of FGFR3 hotspot mutations with tyrosine kinase inhibitors (e.g., erdafitinib) is approved for mUC and requires FGFR3 mutational testing. However, current testing assays (polymerase chain reaction or next-generation sequencing) necessitate high tissue quality, have long turnover time, and are expensive. To overcome these limitations, we develop a deep-learning model that detects FGFR3 mutations using routine hematoxylin-eosin slides. Encompassing 1222 cases, our study is a large-scale validation of a model prescreening FGFR3 mutations for MIBC and mUC patients. In this work, we demonstrate that our model achieves high sensitivity (>93%) on advanced and metastatic cases while reducing molecular testing by 40% on average, thereby offering a cost-effective and rapid pre-screening tool for identifying patients eligible for FGFR3 targeted therapies.
EVALuna2:578143

Analysis of the Impact of Clinical Factors on Low-Intensity Extracorporeal Shockwave Therapy for Erectile Dysfunction - Oginski, Natalie; Apel, Hendrik; Richterstetter, Mario; Lieb, Verena; Fiebig, Christian; Goebell, Peter; Wullich, Bernd; Sikic, Danijel (Urologia Internationalis, 2022)
Introduction: Predictive factors for the treatment success of low-intensity extracorporeal shockwave therapy (Li-ESWT) for erectile dysfunction (ED) are still under debate. Methods: Li-ESWT was performed in 50 patients suffering from ED by applying 3,000 shock waves once a week over a period of 6 weeks. Treatment success was defined as an increase in the International Index of Erectile Function 5 (IIEF-5) score by >= 5 points or an Erectile Hardness Score (EHS) of >= 3 points. IIEF-5 and EHS were measured at baseline and at 3 and 6 months of follow-up. Results: Treatment success according to either the IIEF-5 score or EHS at any time of follow-up was achieved in 28 patients (56%). Twenty-five patients (50%) experienced an improvement during the first 3 months, which lasted for 6 months in 8 cases (16%). Three patients reported improved erectile function only after 6 months. When stratifying the cohort with regard to potential influencing factors, a significantly improved IIEF-5 score could be achieved in men with cardiovascular risk factors (p = 0.026) and in men with antihypertensive medication (p = 0.009). Men without cardiovascular risk factors showed no therapeutic benefit from Li-ESWT. Discussion/Conclusion: Li-ESWT is a valid but often short-lived treatment option for ED, especially in men with cardiovascular risk factors or controlled hypertension. Future studies should assess the feasibility and safety of repeated applications of Li-ESWT.
CRIS-Team WoS Importer:2022-03-04

Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

Combination of GP88 Expression in Tumor Cells and Tumor-Infiltrating Immune Cells Is an Independent Prognostic Factor for Bladder Cancer Patients - Eckstein, Markus; Lieb, Verena; Jung, Rudolf; Sikic, Danijel; Weigelt, Katrin; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Serrero, Ginette; Yue, Binbin; Hartmann, Arndt; et al. (Cells, 2021)
Urothelial bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide and accounts for approximately 3% of global cancer diagnoses. We are interested in prognostic markers that may characterize tumor cells (TCs) and immune cells (ICs) and their relationship in BCa. A potential candidate marker that meets these criteria is progranulin (GP88), which is expressed separately in TCs and ICs. We analyzed GP88 expression by immunohistochemistry (IHC) in 196 muscle-invasive BCa samples using a tissue microarray. The immunoreactive score for GP88 staining in TCs and the percentage of GP88-positive ICs was determined. An easy cutoff for the staining status of TCs (positive vs. negative) and ICs (0% vs. >0%) and, more generally, negative vs. positive GP88 staining could be applied. We detected 93 patients (47.4%) and 92 patients (46.9%) with GP88-positive TCs or ICs, respectively. The IHC results were correlated with clinicopathological and survival data. Positive GP88 staining in TCs appeared to be an independent poor prognostic factor for disease-specific survival (DSS) (RR (relative risk) = 1.74; p = 0.009) and recurrence-free survival (RFS) (RR = 1.92; p = 0.002). In contrast, negative GP88 staining in ICs was an independent negative predictor for overall survival (OS) (RR = 2.18; p < 0.001), DSS (RR = 2.84; p < 0.001) and RFS (RR = 2.91; p < 0.001) in multivariate Cox's regression analysis. When combining GP88 staining in TCs and ICs, a specific combination of GP88-positive TCs and GP88-negative ICs was associated with a 2.54-fold increased risk of death, a 4.21-fold increased risk of disease-specific death and a 4.81-fold increased risk of recurrence compared to GP88-negative TCs and GP88-positive ICs. In summary, GP88 positivity in TCs is a negative prognostic factor for DSS and RFS. In addition, GP88 positivity can mark ICs that are associated with a good prognosis (OS, DSS and RFS). The combination of GP88 staining in TCs and ICs appears to be a significant independent prognostic biomarker in muscle-invasive BCa.
CRIS-Team WoS Importer:2021-08-06

C-reactive protein flare predicts response to anti-PD-(L)1 immune checkpoint blockade in metastatic urothelial carcinoma - Klümper, Niklas; Sikic, Danijel; Saal, Jonas; Büttner, Thomas; Goldschmidt, Franziska; Jarczyk, Jonas; Becker, Philippe; Zeuschner, Philip; Weinke, Maximilian; Kalogirou, Charis; Breyer, Johannes; Burger, Maximilian; et al. (European Journal of Cancer, 2022)
Purpose: Robust biomarkers to predict response to immune checkpoint blockade (ICB) in metastatic urothelial carcinoma (mUC) are still in demand. Recently, early C-reactive protein (CRP) kinetics and especially the novel CRP flare-response phenomenon has been associated with immunotherapy response. Methods: We conducted a multicentre observational study comprising 154 patients with mUC treated with ICB to evaluate the predictive value of a previously described on-treatment CRP kinetics: CRP flare responders (at least doubling of baseline CRP within the first month after initiation of ICB followed by a decline below baseline within three months), CRP responders (decline in baseline CRP by ≥ 30% within three months without a prior flare) and the remaining patients as CRP non-responders. CRP kinetics groups were correlated with baseline parameters, PD-L1 status, progression-free survival (PFS) and overall survival (OS). Results: Objective response was observed in 57.1% of CRP responders, 45.8% of CRP flare responders and 17.9% of CRP non-responders (P < 0.001). CRP flare response was associated with prolonged PFS and OS (P < 0.001). In multivariable Cox regression analysis, CRP flare responders showed a risk reduction of ∼70% for tumour progression and death compared to CRP non-responders. Subgroup analysis of CRP flare responders revealed that patients with a long-flare response (completed flare-response kinetics ≥6 weeks on-treatment) showed even more favourable outcomes following ICB (HR = 0.18, 95%-CI: 0.07–0.48, P < 0.001). Conclusion: CRP (flare)response robustly predicts immunotherapy response and outcomes in mUC independent of PD-L1 status. Thus, early on-treatment CRP kinetics is a promising low-cost and easy-to-implement biomarker to optimise therapy monitoring in patients with mUC treated with ICB.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Biomarker; Bladder cancer; C-reactive protein; CRP flare; CRP flare-Response; Immune checkpoint blockade; Immunotherapy; Long-flare; Metastatic urothelial carcinoma

Digital volumetric assessment of CIS and tumor mass compliments conventional histopathological assessment in muscle-invasive urothelial bladder cancer - Lange, Fabienne; Geppert, Carol-Immanuel; Bahlinger, Veronika; Bertz, Simone; Stöhr, Robert; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Virchows Archiv, 2024)
Carcinoma in situ (CIS) of the bladder is a known parameter regarding the prognosis and recurrence tendency of urothelial carcinomas. Nevertheless, there is little evidence whether the amount of CIS or other precursor lesions, as well as the quantified tumor mass of muscle-invasive urothelial carcinoma, has an influence on the survival or recurrence rate of affected patients. From 80 patients with muscle invasive urothelial bladder cancer and radical cystectomy, 23 samples each were obtained as part of a whole organ mapping in a single institution study, in which the precursor lesions and tumor area were digitally measured and further correlated to pathological standard parameters, patient survival, molecular luminal and basal subtypes, and immune infiltration. Significant correlations were found between tumor mass and surface lining CIS amount for pT-stage, lymphovascular invasion, and perineural infiltration. Furthermore, an increased tumor mass as well as an increased amount of CIS combined with an increased tumor mass showed a significantly reduced survival rate in multivariable analysis (HR = 2.75; P = 0.019 vs. HR = 3.54; P = 0.002) as well as a significantly increased recurrence. No correlations could be found with molecular subtypes and immune infiltration. The exact measurement of the tumor mass with and without the CIS surface area, whether manually or, more specifically, digitally, could be incorporated into routine diagnostics and implemented as an independent predictor for patient post-surgical outcomes. It can therefore serve as an additional predictor for risk stratification and, if necessary, intensified follow-up care or therapy.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Muscle invasive bladder cancer; Prognosis; Radical cystectomy; Survival; Urothelial carcinoma; Urothelial carcinoma in situ

HLA-G expression associates with immune evasion muscle-invasive urothelial cancer and drives prognostic relevance - Branz, Annalena; Matek, Christian; Lange, Fabienne; Bahlinger, Veronika; Klümper, Niklas; Hölzel, Michael; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Wach, Sven; Taubert, Helge; Wullich, Bernd; et al. (Frontiers in Immunology, 2024)
Introduction: Urothelial bladder cancer is frequent and exhibits diverse prognoses influenced by molecular subtypes, urothelial subtype histology, and immune microenvironments. HLA-G, known for immune regulation, displays significant membranous expression in tumor tissues. Methods: We studied the protein expression of Human Leucocyte Antigen G (HLA-G) in 241 Muscle-Invasive Bladder Cancer (MIBC) patients, elucidating its potential clinical and biological significance. Protein expression levels were evaluated and correlated with molecular subtypes, histological characteristics, immune microenvironment markers, and survival outcomes. Results: High HLA-G expression associates with poor overall survival (OS) and diseasespecific survival (DSS), independent of clinicopathological parameters. HLA-G expression varies among molecular subtypes and Urothelial Subtype Histology, e.g., elevated expression levels in basal/squamous MIBC and those with sarcomatoid differentiation. Notably, HLA-G is increased in MIBC with an immune evasive microenvironment (high PD-L1 tumor cell expression, NK cell depletion, granzyme B (GZMB)/CD8 ratio reduction, MHC class I (MHCI) expression reduction) that are characterized by immunosuppressive features and poor prognosis. Furthermore, HLA-G correlates with elevated levels of other immune checkpoint proteins (TIGIT, LAG3, CTLA-4), indicating its role in immune evasion. Discussion: Our findings underscore HLA-G’s role as a potential prognostic marker and interesting immunotherapeutic target in MIBC. Its impact on immune evasion mechanisms and broad expression, coupled with associations withpoor survival and distinct tumor phenotypes, positions HLA-G as a promising protein for further exploration in developing targeted immunotherapies for MIBC patients.
CRIS-Team Scopus Importer:2024-11-15
Keywords: HLA-G; immune checkpoints; immune evasion; immune microenvironment; urothelial cancer

Integration of spatial pd-l1 expression with the tumor immune microenvironment outperforms standard pd-l1 scoring in outcome prediction of urothelial cancer patients - Weyerer, Veronika; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Breyer, Johannes; Bolenz, Christian; Erben, Philipp; et al. (Cancers, 2021)
Background: Immune therapy has gained significant importance in managing urothelial cancer. The value of PD-L1 remains a matter of controversy, thus requiring an in-depth analysis of its biological and clinical relevance. Methods: A total of 193 tumors of muscle-invasive bladder cancer patients (MIBC) were assessed with four PD-L1 assays. PD-L1 scoring results were correlated with data from a comprehensive digital-spatial immune-profiling panel using descriptive statistics, hierarchical clustering and uni-/multivariable survival analyses. Results: PD-L1 scoring algorithms are heterogeneous (agreements from 63.1% to 87.7%), and stems from different constellations of immune and tumor cells (IC/TC). While Ventana IC5% algorithm identifies tumors with high inflammation and favorable baseline prognosis, CPS10 and the TCarea25%/ICarea25% algorithm identify tumors with TC and IC expression. Spatially organized immune phenotypes, which correlate either with high PD-L1 IC expression and favorable prognosis or constitutive PD-L1 TC expression and poor baseline prognosis, cannot be resolved properly by PD-L1 algorithms. PD-L1 negative tumors with relevant immune infiltration can be detected by sTILs scoring on HE slides and digital CD8+ scoring. Conclusions: Contemporary PD-L1 scoring algorithms are not sufficient to resolve spatially distributed MIBC immune phenotypes and their clinical implications. A more comprehensive view of immune phenotypes along with the integration of spatial PD-L1 expression on IC and TC is necessary in order to stratify patients for ICI.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Bladder cancer; Immune phenotypes; PD-1; PD-L1; TILs; Urothelial cancer

Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2024)
BACKGROUND: Grading of muscle-invasive bladder cancer (MIBC) according to the current World Health Organization (WHO) criteria is controversial due to its limited prognostic value. All MIBC cases except a tiny minority are of high grade. OBJECTIVE: To develop a prognostic histological scoring system for MIBC integrating histomorphological phenotype, stromal tumor-infiltrating lymphocytes (sTILs), tumor budding, and growth and spreading patterns. DESIGN, SETTING, AND PARTICIPANTS: Tissue specimens and clinical data of 484 patients receiving cystectomy and lymphadenectomy with curative intent with or without adjuvant chemotherapy. Histomorphological phenotypes, sTILs, tumor budding, and growth and spreading patterns were evaluated and categorized into four grade groups (GGs). GGs were correlated with molecular subtypes, immune infiltration, immune checkpoint expression, extracellular matrix (ECM) remodeling, and epithelial-mesenchymal transition (EMT) activity. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: GGs were associated with overall (OS), disease-specific (DSS), and progression-free (PFS) survival in univariable and multivariable analyses. Association with biological features was analyzed with descriptive statistics. RESULTS AND LIMITATIONS: Integration of two histomorphological tumor groups, three sTILs groups, three tumor budding groups, and four growth/spread patterns yielded four novel GGs that had high significance in the univariable survival analysis (OS, DSS, and PFS). GGs were confirmed as independent prognostic predictors with the greatest effect in the multivariable Cox regression analysis. Correlation with molecular data showed a gradual transition from basal to luminal subtypes from GG1 to GG4; a gradual decrease in survival, immune infiltration, and immune checkpoint activity; and a gradual increase in ECM remodeling and EMT activity. CONCLUSIONS: We propose a novel, prognostically relevant, and biologically based scoring system for MIBC in cystectomies applicable to routine pathological sections. PATIENT SUMMARY: We developed a novel approach to assess the aggressiveness of advanced bladder cancer, which allows improved risk stratification compared with the method currently proposed by the World Health Organization.
EVALuna2:539845

Utility of stromal tumor infiltrating lymphocyte scoring (sTILs) for risk stratification of patients with muscle-invasive urothelial bladder cancer after radical cystectomy - Sikic, Danijel; Weyerer, Veronika; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Schmitz-Draeger, Bernd J.; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Urologic Oncology-Seminars and Original Investigations, 2021)
Background: Multi-omics analyses of muscle-invasive bladder cancer (MIBC) demonstrated that specific patterns of tumor infiltrating lymphocytes (TILs) associates with improved outcomes in patients treated with radical cystectomy. However, methodologies for simple and robust quantification of TILs, especially for daily practice purposes, are lacking. Thus, we investigated the feasibility of stromal TIL scoring on hematoxylin/eosin stained (HE) slides in MIBC. Materials and methods: sTILs were scored on HE whole slides of 241 MIBC patients treated with radical cystectomy and adjuvant chemotherapy. Median infiltration of 10% was used as objective cut-off. Additionally, immunohistochemistry was performed on spatially organized tissue microarrays to quantify key immune cell populations objectively for correlational analyses with sTIL scoring results (CD3+/Pan-T-cells, CD8+/cytotoxic T-Cells, CD56+/NK-cells, CD68+/macrophages). sTILs amounts were correlated with clinicopathological features, recurrence-free (RFS), disease-specific (DSS), and overall survival (OS). Results: sTIL amounts correlated moderately to strongly with quantitatively estimated amounts of pan-T-cells (r = 0.73, P <0.0001), cytotoxic T-cells (r = 0.73, P <0.0001), NK-cells (r = 0.68, P <0.0001), macrophages (r = 0.55, P <0.0001) and with pan-cytotoxic immune infiltration (r = 0.78, P <0.0001), thus reflecting overall infiltration with key immune cell populations. sTIL infiltration ≥10% was associated with significantly higher 5-year OS (45.5% vs. 19.8%), DSS (56.6% vs. 25.6%) and RFS (56.2% vs. 18.9%; P <0.0001 for all three comparisons) rates, and lower pT-stage (P = 0.015), lower pN-stage (P = 0.028), lower rates of lymphovascular invasion (P = 0.0003) and blood vessel invasion (P = 0.01) when compared to sTIL infiltration of <10%. Multivariable regressions models confirmed sTILs as strongest independent predictor for improved outcomes following radical cystectomy. Conclusions: HE based sTIL scoring is a reliable tool to assess MIBC inflammation status and to stratify the survival of MIBC patients undergoing radical cystectomy. sTIL amount is an independent predictor for improved survival, and might be an useful, routinely applicable tool to identify patients benefiting from perioperative platinum-based chemotherapy and checkpoint inhibitor therapy. However, external validation of our data is required.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bladder cancer; Cystectomy; Prognosis; sTILs; TILs; Urothelial cancer